Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fgene.2021.658862
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing of Human Pluripotent Stem Cell-Derived Macrophages for Quality Control of The Cell Therapy Product

Abstract: Macrophages exhibit high plasticity to achieve their roles in maintaining tissue homeostasis, innate immunity, tissue repair and regeneration. Therefore, macrophages are being evaluated for cell-based therapeutics against inflammatory disorders and cancer. To overcome the limitation related to expansion of primary macrophages and cell numbers, human pluripotent stem cell (hPSC)-derived macrophages are considered as an alternative source of primary macrophages for clinical application. However, the quality of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The morphology of iMACs was comparable to that of typical blood monocyte-derived macrophages ( Figure 3 B). FACS analysis revealed that 97.9% of iMACs were double-positive for the macrophage-specific markers CD14 and CD45, and 87.9% of iMACs were double-positive for CD86 and CD45 ( Figure 3 C) [ 17 ]. To evaluate whether iMACs are functional, we performed a phagocytosis assay.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of iMACs was comparable to that of typical blood monocyte-derived macrophages ( Figure 3 B). FACS analysis revealed that 97.9% of iMACs were double-positive for the macrophage-specific markers CD14 and CD45, and 87.9% of iMACs were double-positive for CD86 and CD45 ( Figure 3 C) [ 17 ]. To evaluate whether iMACs are functional, we performed a phagocytosis assay.…”
Section: Resultsmentioning
confidence: 99%
“…Other cells were also clustered using known markers, as follows: keratinocytes were identified by cell cluster expression of KRT1 [ 26 ], KRT14 [ 27 ], and KRT5 [ 28 ]; pericytes [ 29 ] by RGS5, CSPG4, and PDGFRB; T cells by CD3D [ 30 ], CD3E, CD8A, and CD4 [ 31 ]; macrophages by CD163 [ 32 ] and AIF1 [ 33 ]; dendritic cells (DCs) [ 34 ] by CD1C and FCER1A; natural killer (NK) cells by NKG7 [ 35 ]; melanocytes by PMEL [ 36 ]; B cells by IGJ and MS4A1 [ 37 ]; mast cells by TPSAB1 [ 38 ]; eccrine cells by AQP5 [ 39 ] and DCD [ 30 ]; and endothelial and lymphatic endothelial cells by ACKR1 [ 30 ] and LYVE1, respectively [ 40 ]. Further comparison of the 9192 total skin fibroblasts comprised of patient- and control-derived samples identified 12 distinct subclusters, which were annotated using the top DEGs and references to literature ( Figure 2 , Figure 3 and Figure S2 ; Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other cells were also clustered using known markers, as follows: keratinocyte identified by cell cluster expression of KRT1 [26], KRT14 [27], and KRT5 [28]; pe [29] by RGS5, CSPG4, and PDGFRB; T cells by CD3D [30], CD3E, CD8A, and CD macrophages by CD163 [32] and AIF1 [33]; dendritic cells (DCs) [34] by CD1 FCER1A; natural killer (NK) cells by NKG7 [35]; melanocytes by PMEL [36]; B cells and MS4A1 [37]; mast cells by TPSAB1 [38]; eccrine cells by AQP5 [39] and DCD [3 endothelial and lymphatic endothelial cells by ACKR1 [30] and LYVE1, respective These total cells analyzed with Seurat provided unsupervised clustering of 43 cell populations (Figure S1A), all of which included both healthy and LS disbursement (Figure S1B), and then were categorized into 14 main groups of cells using annotations from published gene expression profiles for the different cell types (Figure S1C) (Table S2). Our primary cells of interest, the fibroblasts, were characterized by COL1A1, COL1A2, and PDGFRA expression identified within these clusters (Figure S1D).…”
Section: Attributes Ls Patients (N = 14)mentioning
confidence: 99%
“…The presence of RUNX1 and CD44 in these hematopoietic progenitors further confirmed their definitive identity ( Figure 2 B-D). Previous studies generated macrophages from hPSCs with a typical M-CSF treatment at the later stages of differentiation in the presence of other cytokines, 6 , 17 , 18 , 19 , 20 and other protocols employed M-CSF only after the collection of floating hematopoietic progenitors. 18 , 19 To evaluate whether M-CSF alone is sufficient to induce macrophage differentiation from our hPSC-derived myeloid progenitors, day 12 cells were subjected to further differentiation with or without M-CSF and subjected for flow cytometry analysis of CD14 and CD11b expression at day 32.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies generated macrophages from hPSCs with a typical M-CSF treatment at the later stages of differentiation in the presence of other cytokines, 6 , 17 , 18 , 19 , 20 and other protocols employed M-CSF only after the collection of floating hematopoietic progenitors. 18 , 19 To evaluate whether M-CSF alone is sufficient to induce macrophage differentiation from our hPSC-derived myeloid progenitors, day 12 cells were subjected to further differentiation with or without M-CSF and subjected for flow cytometry analysis of CD14 and CD11b expression at day 32. As expected, the addition of 50 ng/ml M-CSF significantly increased the proportion of CD14+ and CD11b+ cells compared with conditions without M-CSF or with 10 ng/ml M-CSF ( Figure 2 E).…”
Section: Resultsmentioning
confidence: 99%